2009
DOI: 10.1214/ejp.v14-717
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Analysis for Bifurcating AutoRegressive Processes via a Martingale Approach

Abstract: We study the asymptotic behavior of the least squares estimators of the unknown parameters of general pth-order bifurcating autoregressive processes. Under very weak assumptions on the driven noise of the process, namely conditional pair-wise independence and suitable moment conditions, we establish the almost sure convergence of our estimators together with the quadratic strong law and the central limit theorem. All our analysis relies on non-standard asymptotic results for martingales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 15 publications
2
53
0
Order By: Relevance
“…The next result is an adaptation of Lemma A.2 in Bercu et al (2009) to the GW tree framework. It gives a correspondence between sums on one generation and sums on the whole tree.…”
Section: B1 Preliminary Results: From Single-trees To Multiple Treesmentioning
confidence: 91%
See 1 more Smart Citation
“…The next result is an adaptation of Lemma A.2 in Bercu et al (2009) to the GW tree framework. It gives a correspondence between sums on one generation and sums on the whole tree.…”
Section: B1 Preliminary Results: From Single-trees To Multiple Treesmentioning
confidence: 91%
“…An asymmetric BAR model was therefore proposed by Guyon (2007), where the two sets of parameters corresponding to sister cells are allowed to be different. Inference for this model was only investigated for single-trees growing to infinity, see Guyon (2007), Bercu et al (2009) for the fully observed model or Delmas and Marsalle (2010), de Saporta et al (2011), de Saporta et al (2012 for missing data models.…”
Section: Introductionmentioning
confidence: 99%
“…Basawa and Huggins [2,3] and Basawa and Zhou [4,5]. More recently, de Saporta et al [8,19] introduces asymmetry and take into account missing data while Blandin [14], Bercu and Blandin [7], and de Saporta et al [20] study an extension with random coefficients. Bitseki-Penda and Djellout [10] prove deviation inequalities and moderate deviations for estimators of parameters in linear BAR processes.…”
Section: )mentioning
confidence: 99%
“…This enables us to extend the recent results of Doumic et al in several directions: adaptive estimation, extension of the smoothness classes and the loss functions considered, and also a proof of a minimax lower bound. In Section 4.2, we show how bifurcating autoregressive models (BAR) as developped for instance in de Saporta et al [8] and Bitseki Penda and Olivier [13] are embedded into our generic framework of estimation. A numerical illustration highlights the feasibility of our procedure in practice and is presented in Section 4.3.…”
mentioning
confidence: 99%
“…This allowed him to conclude a statistical evidence in aging in E. Coli. Let us also mention [6], where Bercu & Al. using the martingale approach give asymptotic analysis of the least squares estimator of the unknown parameters of a general asymmetric pth-order BAR processes.…”
Section: Introductionmentioning
confidence: 99%